New insights into the ~74 ka Toba eruption from sulfur isotopes of polar ice cores - Crick, Laura; Burke, Andrea; Hutchison, William; Kohno, Mika; Moore, Kathryn; Savarino, Joel; Doyle, Emily; Mahony, Sue; Kipfstuhl, Sepp; Rae, James; Steele, Robert; Sparks, R. Stephen J.; et al. (HAL CCSD, 2021)
Abstract. The ~74 ka Toba eruption was one of the largest volcanic events of the Quaternary. There is much interest in determining the impact of such a huge event, particularly on the climate and hominid populations at the time. Although the Toba eruption has been identified in both land and marine archives as the Youngest Toba Tuff, its precise place in the ice core record is ambiguous. Multiple volcanic sulfate signals have been identified in both Antarctic and Greenland ice cores within the uncertainty of age estimates as possible events for the Toba eruption. We measure sulfur isotope compositions in Antarctic ice samples at high temporal resolution across 11 of these potential Toba sulfate peaks in two cores to identify candidates with sulfur mass-independent fractionation (S-MIF), indicative of an eruption whose plume reached altitudes at or above the ozone layer in the stratosphere. Using this method, we identify several candidate sulfate peaks that contain stratospheric sulfur. We further narrow down potential candidates based on the isotope signatures by identifying sulfate peaks that are due to a volcanic event at tropical latitudes. In one of these sulfate peaks at 73.67 ka, we find the largest ever reported magnitude of S-MIF in volcanic sulfate in polar ice, with a Δ33S value of −4.75 ‰. As there is a positive correlation between the magnitude of the S-MIF signal recorded in ice cores and eruptive plume height, this could be a likely candidate for the Toba supereruption, with a plume height in excess of 45 km. These results support the 73.7 ± 0.3 ka (1σ) ka Ar/Ar age estimate for the eruption, with ice core ages of our candidates with the largest magnitude S-MIF at 73.67 and 73.74 ka. Finally, since these candidate eruptions occurred on the transition into Greenland Stadial 20, the relative timing suggests that Toba was not the trigger for the large Northern Hemisphere cooling at this time although we cannot rule out an amplifying effect.